The Optimal Enforcement of Insider Trading Regulations - DeMarzo, Peter M.; Fishman, Michael J.; Hagerty, Kathleen M. (Journal of Political Economy, 1998)
Regulating insider trading lessens the adverse selection problem facing market makers, enabling them to quote better prices. An Optimal enforcement policy must balance these benefits against the costs of enforcement. Such a policy must specify (i) the conditions under which the regulator conducts an investigation, (ii) the penalty schedule imposed if an insider is caught, and (iii) a transaction tax to fund enforcement. We derive the policy that maximizes investors welfare. This policy entails investigations following large trading volumes or large price movements or both. Insiders caught making large trades are assessed the maximum penalty, but small trades are not penalized. Given this policy, insiders trade most aggressively on news with an intermediate price impact but refrain from trading on moderate or extreme news.